2004
DOI: 10.1126/science.1102160
|View full text |Cite
|
Sign up to set email alerts
|

Activating Mutations of NOTCH1 in Human T Cell Acute Lymphoblastic Leukemia

Abstract: Very rare cases of human T cell acute lymphoblastic leukemia (T-ALL) harbor chromosomal translocations that involve NOTCH1, a gene encoding a transmembrane receptor that regulates normal T cell development. Here, we report that more than 50% of human T-ALLs, including tumors from all major molecular oncogenic subtypes, have activating mutations that involve the extracellular heterodimerization domain and/or the C-terminal PEST domain of NOTCH1. These findings greatly expand the role of activated NOTCH1 in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

84
2,577
12
18

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,496 publications
(2,730 citation statements)
references
References 23 publications
84
2,577
12
18
Order By: Relevance
“…In our study, although we noted that the Notch 2 locus (1p13-11) in Mary-X was moderately amplified on array comparative genomic hybridization, the Notch 3 locus was not amplified. It had also been demonstrated that mutations within Notch receptors can activate signaling in the absence of a ligand (Sanchez-Irizarry et al, 2004;Weng et al, 2004;Gordon et al, 2007). However, we did not find these gain-of-function mutations in Notch 3 in Mary-X.…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Alcontrasting
confidence: 76%
“…In our study, although we noted that the Notch 2 locus (1p13-11) in Mary-X was moderately amplified on array comparative genomic hybridization, the Notch 3 locus was not amplified. It had also been demonstrated that mutations within Notch receptors can activate signaling in the absence of a ligand (Sanchez-Irizarry et al, 2004;Weng et al, 2004;Gordon et al, 2007). However, we did not find these gain-of-function mutations in Notch 3 in Mary-X.…”
Section: Notch 3 Dependency Of Ibc Embolus Y Xiao Et Alcontrasting
confidence: 76%
“…This is in contrast to the NOTCH1 alteration pattern revealed in hematopoietic malignancies, where Notch is known as tumor suppressor 4, 89. The majority of these mutations include missense mutations in the NRR domain and nonsense/frame‐shift ones in the PEST domain (Fig.…”
Section: A Complete View Of Notch1 Mutations Across Sccsmentioning
confidence: 88%
“…In support of this, many studies in mice have subsequently revealed that expression of constitutive-active Notch proteins leads to potent and specific induction of T-ALL [158]. Aster and colleagues searched for specific Notch1 mutations in T-ALLs that do not harbor the t(7;9) translocation and identified two hotspot regions in the Notch1 gene: the heterodimerization and the PEST-domain [159]. Mutations in the heterodimerization domain enhance S3 cleavage of Notch and cause, via augmented NICD production, a significant increase in Notch signaling.…”
Section: Notch and Leukemiamentioning
confidence: 97%
“…Genetic and biochemical data suggest that loss of the PEST-domain enhance NICD protein stability, reviewed in [160]. Synergistic heterodimerization and PEST domain mutants are found together in cis in 10 -20 % of human T-ALLs [159] and low copy number amplification of Notch1 has also been reported [161]. Notch mutations appear to collaborate with a diverse collection of other proteins dysregulated in T-ALL.…”
Section: Notch and Leukemiamentioning
confidence: 99%